The Impact of Search, Solve, Create and Share (SSCS) Learning Model On Mathematical Visual Representation Ability Of Junior High School Students - Nurjannah, D; Prabawanto, S (International Conference on Elementary Education, 2020)
Representation ability is one of the important abilities that should be developed by students. Based on the some reports, it can be seen that the students’ visual representation ability is still low. It is necessary to apply a learning model that can improve the students’ ability. The learning model that can be predicted to improve the students’ ability is Search, Solve, Create, and Share (SSCS). This research aims to find out whether the junior high school students achievement of representation ability of mathematical visual is better than the students who got conventional learning. The method of this research was a quasi experiment method. There were two groups in this research, the first was experimental group who used Search, Solve, Create and Share (SSCS) learning model and the second was control group that used conventional learning model. The instument for collecting data were instrument of representation ability of mathematical visual and observation sheet. The result of this study showe that students who got Search, Solve, Create and Share (SSCS) learning model are better than students who got conventional learning model